2005
DOI: 10.1007/s11270-005-4589-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tropospheric Ozone on Potato Plants Protected by the Antioxidant Diphenylamine (DPA)

Abstract: To assess the protective effects of diphenylamine (DPA) on yield, DPA-and non-DPAtreated plants of potatoes (Solanum tuberosum cv. Agria) were exposed to ambient air at a rural site in Spain. Concentrations of ambient ozone were high at the site. Untreated plants served as controls. The DPA treatments did not have a significant effect on Chl content. The treatment with DPA (0.2 M) caused a significant increase of fresh weight production and tuber number of the potato plants in both years of study (32 and 47% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…When sprayed onto poinsettia plants, the fungicides benomyl and diphenylamine (DPA) reduced O 3 injury . Similar results were achieved with pinto bean (Pell 1976), potato (Carrasco-Rodriguez et al 2005) and tobacco (Reinert and Spurr 1972) plants. Gilbert et al (1975) reported that dust and liquid applications of DPA on apple, and dust application of DPA on bean, muskmelon and petunia also provided protection against O 3 injury.…”
Section: The Chemistry Of O 3 Formation and Its Uptake And Fate In Psupporting
confidence: 84%
See 1 more Smart Citation
“…When sprayed onto poinsettia plants, the fungicides benomyl and diphenylamine (DPA) reduced O 3 injury . Similar results were achieved with pinto bean (Pell 1976), potato (Carrasco-Rodriguez et al 2005) and tobacco (Reinert and Spurr 1972) plants. Gilbert et al (1975) reported that dust and liquid applications of DPA on apple, and dust application of DPA on bean, muskmelon and petunia also provided protection against O 3 injury.…”
Section: The Chemistry Of O 3 Formation and Its Uptake And Fate In Psupporting
confidence: 84%
“…A foliar spray of DPA at 1,000 ppm onto apple and at 1 % in bean, melon, petunia and tobacco reduced O 3 damage by 50 % or more (Lisk 1975). Carrasco-Rodriguez et al (2005) recorded an increase in fresh biomass and tuber numbers of potato after DPA was applied. Fuhrer et al (1992) (continued)…”
Section: The Chemistry Of O 3 Formation and Its Uptake And Fate In Pmentioning
confidence: 97%
“…When sprayed onto poinsettia plants, the fungicides benomyl and diphenylamine (DPA) reduced O 3 injury . Similar results were achieved with pinto bean (Pell 1976), potato (Carrasco- Rodriguez et al 2005) and tobacco (Reinert and Spurr 1972) plants. Gilbert et al (1975) reported that dust and liquid applications of DPA on apple, and dust application of DPA on bean, muskmelon and petunia also provided protection against O 3 injury.…”
Section: Rossupporting
confidence: 82%
“…A foliar spray of DPA at 1,000 ppm onto apple and at 1 % in bean, melon, petunia and tobacco reduced O 3 damage by 50 % or more (Lisk 1975). Carrasco- Rodriguez et al (2005) recorded an increase in fresh biomass and tuber numbers of potato after DPA was applied. ) 10 days …”
Section: Rosmentioning
confidence: 96%
“…ethylenediurea EDU) or resistance inducers able to modulate oxidative burst, such as functional analogues of SA (i.e. benzothiadiazole, BTH), may counteract the ozone injury, thus improving the plant tolerance (Iriti et al 2003;Manning et al 2003, Carrasco-Rodriguez et al 2005Hassan 2006). …”
Section: Resultsmentioning
confidence: 99%